Faktor Faktor Yang Mempengaruhi ketahanan Terhadap Tekanan Audit - Rama Elvia Wira Foliya; Hasnawati (Postgraduate Management Journal, 2023)
The purposee of this studyy was to examine the effect of certification, training, objectivity on audit pressure. This research is includedd in quantitativee rresearch. The method of collection is by using a questionnaire which is distributed to respondents whoo work at the Public Accountingg Firm (KAP) in Jakarta. Questionnaires were distributed via google form and which can be used for further analysis as many as 150. This study uses convenience sampling. Data analysis using multiple regression with the help of SPSS version 24.0 for Windows. The object used is a Public Accounting Firm (KAP) employee in Jakarta. The resultss of this study indicatee that the Auditor Certification variable has a positive effect onn audit resilience, while the Training and Objectivity variables have no effect on audit pressure.